2017
DOI: 10.18203/2349-2902.isj20174488
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of C-reactive protein and neutrophil-limphocyte ratio in perforated appendicitis at Hasan Sadikin Hospital Bandung

Abstract: Background: The diagnosis of appendicitis depends on the subjective criteria of clinical examination. However, distinguishing acute perforated appendicitis (local peritonitis) and non-perforated is often difficult especially in the elderly population that usually not clinically specific unless it has developed into generalized peritonitis. Between the non-perforated acute appendicitis and perforate should be distinguished because of different surgical approaches. C-reactive protein (CRP) and neutrophil-lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…It showed that NLR increased in appendicitis and further increases as the inflammation progresses. This result is consistent with the findings of previous studies (12, 24, 25). Although TWBC showed a significant association with appendicitis, NLR proved superior and has greater diagnostic accuracy compared to TWBC alone (16, 26, 27).…”
Section: Discussionsupporting
confidence: 94%
“…It showed that NLR increased in appendicitis and further increases as the inflammation progresses. This result is consistent with the findings of previous studies (12, 24, 25). Although TWBC showed a significant association with appendicitis, NLR proved superior and has greater diagnostic accuracy compared to TWBC alone (16, 26, 27).…”
Section: Discussionsupporting
confidence: 94%
“…NLR was shown to be elevated in appendicitis, and this elevation continued as inflammation worsened. This finding agrees with those of past research [ 19 , 20 ]. Despite the apparent correlation between WBC and appendicitis, NLR has been shown to be greater and to have higher diagnostic accuracy than WBC solely [ 21 ], and this is reinforced in this study.…”
Section: Discussionsupporting
confidence: 94%
“…There are studies reporting different results and cut-off values on the diagnostic value of inflammatory markers such as leukocytes, neutrophils, and CRP measured from blood. [14][15][16] In a study conducted by Yang et al [17] perforated AA, both WBC counts and CRP levels were found to be significantly higher than non-perforated AA in patients with perforated AA. Similarly, Guraya et al [18] also found significantly higher WBC values in complex (gangrenous, perforated) appendicitis compared to AA.…”
Section: Discussionmentioning
confidence: 99%